36. THE CURRENT STATUS OF OVERWEIGHT AND OBESITY IN WOMEN OF REPRODUCTIVE AGE 15-49 IN TWO COMMUNES OF DINH HOA DISTRICT, THAI NGUYEN PROVINCE AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the current status of overweight and obesity in women of reproductive age 15-49 in 2 communes of Dinh Hoa district, Thai Nguyen province in 2024 and analyze some related factors.Research subjects and methods: The study was conducted using a descriptive method with a cross-sectional design on women of  reproductive age 15-49 in 2 communes of Dinh Hoa district, Thai Nguyen province.Research results: The overall rate of overweight and obese women of  reproductive age age was 7.3%, of which overweight accounted for 4.7% and obesity accounted for 2.6%. In the total number of women of reproductive age, the 35-49 age group had the highest rate of overweight and obesity (3.7%), of which overweight was 2.4% and obesity was 1.3%; followed by the 25-34 age group with 3.1% (overweight was 2.0% and obesity was 1.1%), with the lowest rate being the 15-24 age group with 0.4%. The highest rate of overweight and obesity was in the Tay ethnic group at 5.4% (of which overweight accounted for 3.7% and obesity was 1.7%), followed by the Kinh ethnic group with the rate of overweight and obesity of 1.1% and the lowest rate was in the other ethnic groups at 0.7%. There was a relationship between the group of education level, family history of overweight and obesity, knowledge and practice of overweight and obesity prevention with the overweight and obesity status of the study subjects.
Keywords: Overweight; obesity; related factors; women of reproductive age 15-49.